2021
DOI: 10.1172/jci146031
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive tracking of circulating viral RNA through all stages of SARS-CoV-2 infection

Abstract: Background: Circulating SARS-CoV-2 RNA may represent a more reliable indicator of infection than nasal RNA, but RT-qPCR lacks diagnostic sensitivity for blood samples. Methods: A CRISPR-augmented RT-PCR assay that sensitively detects SARS-CoV-2 RNA was employed to analyze viral RNA kinetics in longitudinal plasma samples from nonhuman primates (NHP) after virus exposure; to evaluate the utility of blood SARS-CoV-2 RNA detection for COVID-19 diagnosis in adults cases confirmed by nasal/nasopharyngeal swab RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
(39 reference statements)
2
25
0
Order By: Relevance
“…Care of the patient required no organ biopsies, and we found no viral RNA in peripheral blood cells (not shown). Nevertheless, our data strongly point to RNAemia as a proxy for severe infection, as also proposed by others 22 , and perhaps as a tool to monitor viral clearance systemically to identify cases of post-acute viral persistence, which may potentially lead to protracted symptoms 55 .…”
Section: Discussionsupporting
confidence: 77%
“…Care of the patient required no organ biopsies, and we found no viral RNA in peripheral blood cells (not shown). Nevertheless, our data strongly point to RNAemia as a proxy for severe infection, as also proposed by others 22 , and perhaps as a tool to monitor viral clearance systemically to identify cases of post-acute viral persistence, which may potentially lead to protracted symptoms 55 .…”
Section: Discussionsupporting
confidence: 77%
“…In our study, we demonstrated the presence of viral components in 13 out of 24 patients (54.17%) by plasma RT-PCR. However, RT-qPCR has been reported to exhibit poor and highly variable diagnostic sensitivity (1–40%) when employed to detect SARS-CoV-2 RNA in blood samples from confirmed COVID-19 cases, with most positive samples exhibiting high Ct values indicative of a low viral RNA concentration [ 18 ]. More research is needed to shed light on the prognostic significance of plasma viral RNA in COVID-19 patients and its relationship with predictive factors.…”
Section: Discussionmentioning
confidence: 99%
“…The FXIIa is one of the main proteins of the contact system (CS), which is an innate inflammatory defense mechanism orchestrated against any negatively charged foreign or misfolded proteins, or nucleic acids such as DNA or RNA or microorganisms such as viruses, found in the intravascular niche [ 105 , 106 ]. This speculates that either the whole coronaviruses, which contains conserved negatively charged amino acids located within domain III in the carboxyl end of nucleocapsid proteins [ 107 ] or the SARS-CoV-2 RNA that are circulating in the bloodstream [ 108 ] are readily capable of inducing FXII-associated intrinsic coagulation pathway to form a pathological thrombus [ 104 ]. In fact, a pulmonary vessel wall isolated from COVID-19 positive lung tissues exhibited increased expression and activity of FXIIa [ 109 ], showing the commencement of the pathogenic pro-coagulant chain.…”
Section: Sars-cov-2 and Its Receptors In Blood Vessel Pathophysiologymentioning
confidence: 99%